Hubungan antara Konflik Peran dan Ambiguitas Peran dengan Kinerja Perawat Wanita - Sepda Dwi Putri; Harri Kurniawan (Psyche 165 Journal, 2019)
This study aims to determine the relationship between role conflict and role ambiguity with the performance of female nurses in Sungai Dareh Dharmasraya Hospital. The independent variables in this study are role conflict and role ambiguity and the dependent variable is performance. The measuring instrument used in this study is the scale of role conflict, role ambiguity scale, and scale of performance. The sampling technique in this study used atechnique saturated sampling. The sample in this study were 70 female nurses in Sungai Dareh Dharmasraya Hospital. Validity and reliability test in this study using technique Alpha Cronbach. The results of the validity coefficient on the movable role conflict scale from rix = 0.405 to rix = 0.817 with the reliability coefficient α = 0.945 while on the moving role ambiguity scale from rix = 0.349 to rix = 0.945 with the reliability coefficient α = 0.971 and at the moving performance scale from rix = 0.381 to rix = 0.774 with the reliability coefficient α = 0.943. Based on data analysis, the value of the correlation between role conflict and performance was -0.439 with a significance level of 0.000 and the correlation value between role ambiguity and performance was -0.310 with a significance level of 0.009 and the correlation value between role conflict and role ambiguity simultaneously with performance of 0.461 with significance level 0,000 which means the hypothesis is accepted. This shows that there is a significant relationship between role conflict and role ambiguity with the performance of female nurses in Sungai Dareh Dharmasraya Hospital.